2018
DOI: 10.3390/met8110947
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Cooling Performance of Newly Developed Slice Die in the Hot Press Forming Process

Abstract: The cooling performance of a slice die is studied numerically and experimentally. The slice die is designed to improve the cooling performance compared to that of a conventional die that is generally used in the Hot Press Forming (HPF) process by modifying the cooling channel layout and arrangement. In order to understand the physical phenomenon of the slice die cooling performance, the cooling performance of the conventional die is also simulated and their results are compared with the slice die results. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…The design and efficiency of the cooling channels depend mainly on the channel diameter (∅), distance from the cooling channels to the tool surface (s), and distance between the channels (d) [1,2,4,5]. Thus, designing the maximum possible cooling channels for relatively thick parts is a good solution in terms of cooling, but increases the cost of the tool.…”
Section: Cooling Design: Distance From the Cooling Channels To The Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The design and efficiency of the cooling channels depend mainly on the channel diameter (∅), distance from the cooling channels to the tool surface (s), and distance between the channels (d) [1,2,4,5]. Thus, designing the maximum possible cooling channels for relatively thick parts is a good solution in terms of cooling, but increases the cost of the tool.…”
Section: Cooling Design: Distance From the Cooling Channels To The Tomentioning
confidence: 99%
“…The current industrial investment applied to the improvement of this process factor has been documented in numerous published works focused on cooling strategies and contact heat transfer improvement. Recent developments in enhanced conformal cooling strategies involve, among others, additive manufacturing of cooling channels [3], their geometrical optimization [4], and the use of alternative die manufacturing processes to improve channel positioning [5]. Studies considering the heat exchange rate associated with the contact between the die and steel sheet may be classified as experimental [6][7][8][9] and theoretical [10,11] approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [22] showed high hardness and minimum springback of a hot-stamped part by using rapid cooling to a forming temperature between 700 and 750 • C after ejecting from the furnace. Lee et al [23] designed a slice die to improve the cooling rate of the blank during hot stamping and the quenching process.…”
Section: Introductionmentioning
confidence: 99%